Barriers for which the craft beer industry does not take off in Peru - Quispe Orejón, Eleazar Roberto (2018)
This research was conducted in order to understand the barriers that Peruvian entrepreneurs craft beer, which prevents increasing their production supply. To meet this impact a questionnaire and interviews with producers of craft beer consumers in metropolitan Lima and a market segment was applied, being the preference of entrepreneurs to carry out promotion and advertising on social networks is inefficient. A significant percentage of entrepreneurs focuses its products to a broad market segment. The mixed system of payment of excise tax is seen as unfair by the entrepreneur and considered an element that raises the price of its products. The consumer appreciates the taste of beer attribute and shows its willingness to pay a high price.